(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Zeolite can be synthesized from different substances but because of the environmental issues researchers have currently drawn their attention to cost effective and eco-friendly materials that can be used in the synthesis of various zeolites. Kaolin is one of these materials because of their nonhazardous and easy handling property. The uniqueness properties of the material gives it wide range of applications in different fields such as gas separation, adsorption and catalysis.. ZSM-5 Zeolite was prepared by addition of (ethylenediamine) as organic template. This experiment was conducted at the optimum conditions at 160 0c for a period of 44hr. Zeolite synthesized from Kaolin is also a crystalline micro porous aluminosilicate solid consisting of pores and routes of a molecular size. The synthesized material was found to have high SiO2 content of 42.95% and the alumina content of 2.65% which gives the SiO2/Al2O3 ratio of 16.2.In order to obtain a comprehensive picture of morphology of the synthesized material, spectroscopic analysis were performed sing X-ray powder diffraction (XRD) shows peaks at 2Î¸ = 7-9Â° and 22- 25Â°, which correspond to the specific peaks of ZSM-5. Fourier-transform infrared spectroscopy (FTIR) which shows the absorption band near 450 cm-1 is due to the T-O bending vibrations of the SiO4 and AlO4 in tetrahedra. scanning electron microscope (SEM) in this zeolite was crystallized in spherical to cubical shape.